1999
DOI: 10.1557/proc-595-f99w2.3
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of GaN with Buried Tungsten (W) Structures Using Epitaxial Lateral Overgrowth (ELO) via LP-MOVPE

Abstract: A buried tungsten (W) mask structure with GaN is successfully obtained by epitaxial lateral overgrowth (ELO) technique via low-pressure metalorganic vapor phase epitaxy (LP-MOVPE). The selectivity of GaN growth on the window region vs. the mask region is good. An underlying GaN with a striped W metal mask is easily decomposed above 500 °C by the W catalytic effect, by which radical hydrogen is reacted with GaN. It is difficult to bury the W mask because severe damage occurs in the GaN epilayer under the mask. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…To improve the ELOG process the nucleation of GaN on the mask material must be prevented. It is known from MOVPE growth [15] that tungsten masks act as a catalyst for decomposition of GaN by hydrogen radicals. Therefore, we used sputtered WSiN as mask material.…”
Section: Resultsmentioning
confidence: 99%
“…To improve the ELOG process the nucleation of GaN on the mask material must be prevented. It is known from MOVPE growth [15] that tungsten masks act as a catalyst for decomposition of GaN by hydrogen radicals. Therefore, we used sputtered WSiN as mask material.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulties in achieving continuous long-duration HVPE-GaN growth are largely caused by "parasitic reactions"-in the case of HVPE-GaN growth, this denotes unintended polycrystal formation on hightemperature reactor components in the system. There are some reports that tungsten 17,18) and its carbide 19) possess catalytic activity for the decomposition of GaN and to suppress this parasitic reaction. However, tungsten, as well as tungsten carbide (WC), is a hard/brittle material, so components with complex shapes made of these materials cannot be provided.…”
mentioning
confidence: 99%
“…Despite these successful demonstrations in improved device performance on LEO GaN, some difficulties still remain in controlling the structural properties of the overgrown layer. For LEO GaN layers, threading dislocations at the seed (window) region and crystallographic tilt at the lateral overgrown region were typically observed [1,2,[12][13][14][15]. Pendeo-epitaxy with a dielectric mask, which is a new approach to the LEO technique, has been developed by employing a four to five times larger lateral growth rate of the regrown GaN from sidewalls of rectangular stripes compared with that of conventional LEO GaN layers [6,7].…”
mentioning
confidence: 99%
“…Pendeo-epitaxy with a dielectric mask, which is a new approach to the LEO technique, has been developed by employing a four to five times larger lateral growth rate of the regrown GaN from sidewalls of rectangular stripes compared with that of conventional LEO GaN layers [6,7]. However, it was found that mask materials at the window region, which could deteriorate or react during growth, were presumed to affect crystallographic tilt and create significant problems for the coalescence fronts which form tilt boundaries [6,7,12,13]. The degree of crystallographic tilt in dielectric mask-removed Pendeo-epitaxial GaN layers was found to reduce due to elimination of the interface between dielectric masks and laterally grown GaN layers [7,15].…”
mentioning
confidence: 99%